Evaluation of the antidepressant- and anxiolytic-like effects of a hydrophilic extract from the green seaweed Ulva sp. in rats. (21st April 2018) - Violle, Nicolas; Rozan, Pascale; Demais, Hervé; Nyvall Collen, Pi; Bisson, Jean-François
Abstract : Objectives: The green seaweed Ulva sp . contains a large amount of ulvans, a family of sulphated polysaccharides. The present study was designed to investigate in rats the antidepressant- and anxiolytic-like effects of a hydrophilic extract of Ulva sp. (MSP) containing about 45% of ulvans. Methods: After a 14-day administration of MSP at doses of 10, 20 and 40 mg/kg/day, 48 and 60 male adult Wistar rats were respectively tested in the elevated plus-maze (EPM) and the forced swimming test (FST). In the FST, MSP effects were compared to the reference antidepressant drug imipramine (IMI) (10 mg/kg/day). Acute and sub-chronic toxicities of the extract were also assessed in male and female rats following OECD guidelines. Results: MSP treatment did not modify anxiety-related behaviour in the EPM. In contrast, MSP induced a dose-dependent reduction of immobility behaviour in the FST. At the highest tested dose of 40 mg/kg, MSP displayed a significant antidepressant-like effect similar to IMI. MSP did not modify the exploratory behaviour of rats in the open field test and did not produce any toxic effect. Discussion: MSP may potentially represent a good adjunct or alternative to existing antidepressant therapeutics. Further studies are necessary to confirm the mechanism of action of MSP and its modulation of brain functioning.